Odpowiedzi

Najlepsza Odpowiedź!
2010-01-12T22:43:33+01:00
A) (0,4) i (4,0)
podstawiamy do ogólnego wzoru y=ax+b i układamy układ równań
4=a×0+b
0=a×4+b

b=4
0=4a+b

b=4
4a=-b

b=4
4a=-4/:4

b=4
a=-1
y=-1x+4

B) (-2,-2) i (-6,-8)
-2=a×(-2)+b
-8=a×(-6)+b

-2=-2a+b
-8=-6a+b

b=-2+2a
-8=-6a+b

-8=-6a+2a-2
-8=-4a-2
-4a=-8+2
-4a=-6/:(-4)
a=1½

b=2a-2
b=2×1½-2
b=3-2
b=1
y=1½x+1

C) (3,2) i (5,-5)
2=a×3+b
-5=a×5+b

2=3a+b /(-1)
-5=5a+b

-2=-3a-b
-5=5a+b

-7=2a /:2
a=-3½
b=-3a+2
b=-3×(-3½)+2
b=10½+2
b=12½
y=-3½x+12½